Validitas Lembar Kerja Peserta Didik Berbasis Problem Based Learning pada Materi Ekosistem Fase E SMA/MA - Oktavia, Nia; Nurhadi, Nurhadi; Maizeli, Annika (Biocaster : Jurnal Kajian Biologi, 2025)
The biology learning process utilizes a variety of teaching materials, including package books and Student Worksheets (LKPD). However, the LKPD used by teachers is still limited to practicum activities and has not met the components of the preparation of the LKPD optimally. To overcome this, LKPD based on Problem Based Learning (PBL) was developed which has the advantage of improving students' ability to solve problems contextually. This research aims to produce PBL-based LKPD on ecosystem materials that are valid for students in phase E of high school/ma. Development is carried out using a 4D model which includes the stages of defining, design, develop, and disseminate. The research was limited to the development stage with a validity test through filling out a questionnaire by three expert lecturers. The validation results showed that LKPD was in the very valid category with a score of 86.99%. Thus, the PBL-based LKPD developed is declared suitable for use as teaching materials in biology learning.